EPIDEMIOLOGY, CLINICAL FEATURES, TREATMENT, AND PREVENTION OF «TORCH INFECTIONS»: A LITERATURE REVIEW - Oxnorova Sabrina Qaxxor qizi; Xamidova Muhlisa Alisher qizi; Seytnazarov Miyribek Maxsetovich (Scholar Express Journals, 2026)
This article presents information on the current relevance of TORCH infections, their prevalence among the population, and routes of transmission. The impact of the disease on the health of the mother and fetus during pregnancy, as well as its consequences, has been studied. The infection is mainly transmitted through sexual contact and has an adverse effect on the fetus during pregnancy. It occurs with equal frequency among men and women. The incidence is more commonly observed beginning from puberty. The incubation period ranges from 5 to 23 days. The first signs of infection may appear during the intrauterine period of pregnancy, at birth, in infancy, or even years later.
Keywords: TORCH infection; toxoplasmosis; hepatitis B